The academic–vocational divide in three Nordic countries: implications for social class and gender. Issue 1 (2nd January 2018) - Nylund, Mattias; Rosvall, Per-Åke; Eiríksdóttir, Elsa; Holm, Ann-Sofie; Isopahkala-Bouret, Ulpukka; Niemi, Anna-Maija; Ragnarsdóttir, Guðrún
ABSTRACT: In this study we examine how the academic–vocational divide is manifested today in Finland, Iceland and Sweden in the division between vocationally (VET) and academicallyoriented programmes at the upper-secondary school level. The paper is based on a critical re-analysis of results from previous studies; in it we investigate the implications of this divide for class and gender inequalities. The theoretical lens used for the synthesis is based on Bernstein´s theory of pedagogic codes. In the re-analysis we draw on previous studies of policy, curriculum and educational praxis as well as official statistics. The main conclusions are that contemporary policy and curriculum trends in all three countries are dominated by a neo-liberal discourse stressing principles such as "market relevance" and employability. This trend strengthens the academic–vocational divide, mainly through an organisation of knowledge in VET that separates it from more general and theoretical elements. This trend also seems to affect VET students' transitions in terms of reduced access to higher education, particularly in male-dominated programmes. We also identify low expectations for VET students, manifested through choice of textbooks and tasks, organisation of teacher teams and the advice of career counsellors.